Real‐Time Investigation of Intercalation and Structure Evolution in Printed Polymer:Fullerene Bulk Heterojunction Thin Films. Issue 5 (20th December 2015) - Kassar, Thaer; Güldal, Nusret S.; Berlinghof, Marvin; Ameri, Tayebeh; Kratzer, Andreas; Schroeder, Bob C.; Destri, Giovanni Li; Hirsch, Andreas; Heeney, Martin; McCulloch, Iain; Brabec, Christoph J.; Unruh, Tobias
Abstract : The complex intermixing morphology is critical for the performance of the nanostructured polymer:fullerene bulk heterojunction (BHJ) solar cells. Here, time resolved in situ grazing incidence X‐ray diffraction and grazing incidence small angle X‐ray scattering are used to track the structure formation of BHJ thin films formed from the donor polymer poly(2, 5‐bis(3‐hexadecylthiophen‐2‐yl)thieno[3, 2‐ b ]thiophene) with different fullerene derivative acceptors. The formation of stable bimolecular crystals through the intercalation of fullerene molecules between the side chains of polymer crystallites is investigated. Such systems exhibit more efficient exciton dissociation but lower photo‐conductance and faster decay of charges. On the basis of the experimental observations, intercalation obviously takes place before or with the formation of the crystalline polymer domains. It results in more stable structures whose volume remains constant upon further drying. Three distinct periods of drying are observed and the formation of unidimensional fullerene channels along the π‐stacking direction of polymer crystallites is confirmed. Abstract : Real‐time grazing incidence X‐ray scattering measurements using a fully automated sample cell show that bimolecular crystals in printed thin films keep their volume upon drying due to the intercalation of fullerene molecules between side chains of the polymer even when finalizing the drying in vacuum. Intercalation speeds up the drying process resulting in stable morphologies in less than 1 min.